Climate migration in Humayun Kabir’s Men and Rivers: The Padma and Faridpur - Hasan, Md. Mahmudul (SAGE, 2024)
The intensely precarious integration in many parts of Bangladesh between life, rivers and water has been reflected in the country’s river novels that describe the experiences of fishermen and riparian peasants. Among river systems in Bangladesh, the Padma (the Ganges in India) has inspired the greatest number of artists and their writing. Humayun Kabir’s Men and Rivers (1945) stands out as a climate document on the life of the peasantry, whose survival and livelihoods are entwined with this river. However, this novel has remained inadequately known and has not garnered sufficient critical attention in recent years. Filling a lacuna in South Asian literary studies, and combining such studies with climate change discourses, this article discusses Kabir’s novel as a document depicting the environmental challenges faced in Bangladesh, exploring why this literary work has not received prominent coverage.